(untitled) - Bedford, Anthony (Menlo Park, Calif., 1998)
Contents: Motion of a point; Force, mass and acceleration; Energy methods; Momentum methods; Planar kinematics of rigid bodies...
Keywords: Mechanics,Cơ khí